2019
DOI: 10.1063/1.5126135
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive hydrogen detection using curvature change of wireless-electrodeless quartz resonators

Abstract: Hydrogen-gas sensing at low concentrations using extremely narrow gap palladium nanoclusters prepared by resistive spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Other critical thickness, such as 10 µm and 20 µm have also been reported [28,29]. In our previous study, the evaluation of reaction constant performed on a 200 nm thick palladium film yielded an activation energy of 0.372 eV [20], indicating that the surface-to-subsurface transition is the rate-limiting step in this thickness.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Other critical thickness, such as 10 µm and 20 µm have also been reported [28,29]. In our previous study, the evaluation of reaction constant performed on a 200 nm thick palladium film yielded an activation energy of 0.372 eV [20], indicating that the surface-to-subsurface transition is the rate-limiting step in this thickness.…”
Section: Introductionmentioning
confidence: 67%
“…When hydrogen is adsorbed in the palladium film, it expands and causes bending deformation of the resonator. We previously found that the increase in the resonator curvature results in the decrease in the resonance frequency for an AT-cut quartz plate [20]. Therefore, the frequency decrease during exposure to hydrogen gas indicates the progress of the absorption reaction of hydrogen in the palladium film.…”
Section: Hydrogen Absorption Kinetics On Plasma Treated Palladium Filmmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, the palladium nanotube arrays 20 show the resistance change of 247% at 100 ppm, which is larger than the value obtained in the present study, but the response time is 400 s, which is longer than the value observed in the present study. Using the metal oxide semiconductor field-effect transistor (MOSFET), 23 heterojunction field-effect transistor (HFET), 22 surface acoustic wave, 27 and quartz oscillator, 28 in addition to the above sensors, hydrogen gas at 100 ppm and lower concentrations is detectable. The MOSFET and HFET sensors are generally operated at elevated temperatures to accelerate the response.…”
Section: Resultsmentioning
confidence: 99%